Effects of active, passive, or no warm-up on the physiological response to heavy exercise - Ingjer, F.; Stromme, S. B. (European Journal of Applied Physiology, 1979)
Three types of warm-ups were described: 1.Passive warm-ups 2.General/non-specific warm-ups 3.Specific warm-ups Some remarks: a. the nature of the activities depends upon the event and the individual; b. a 1 to 2 degrees Celsius increase in central core temperature is desirable; c. a light sweat over the entire body is the best indicator of the correct temperature; d. fatigue in the warm-up should be avoided; and e. the benefits of the warm-up are lost after between 5 and 45 minutes of rest. Once a specific warm-up is completed the athlete should remain active